2020
DOI: 10.3792/pjaa.96.009
|View full text |Cite
|
Sign up to set email alerts
|

New results on slowly varying functions in the Zygmund sense

Abstract: Very recently Seneta [15] has provided a characterization of slowly varying functions L in the Zygmund sense by using the condition, for each y > 0,We extend this result by considering a wider class of functions and a more general condition than (1). Further, a representation theorem for this wider class is provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…in y, are presented. This limit generalizes the ones analyzed by Seneta [4] and Omey and Cadena [5], both of them being related to the monotony of functions in the Zygmund sense. Under this analysis, properties of θ(y) are described.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…in y, are presented. This limit generalizes the ones analyzed by Seneta [4] and Omey and Cadena [5], both of them being related to the monotony of functions in the Zygmund sense. Under this analysis, properties of θ(y) are described.…”
Section: Discussionsupporting
confidence: 83%
“…In [5], we found that relations of the form in Equation ( 1) hold with limit function θ(x) = 0. In that case, we have…”
Section: Third Formmentioning
confidence: 97%
See 2 more Smart Citations
“…Nowadays, Kevei in [Kevei(2021)] presented an extension of such a conjecture and its proof. Coincidentally, we have been working on such a subject as a part of other researches related to results shown by [Seneta(2019)], see [Omey and Cadena(2020a)] and [Omey and Cadena(2020b)]. Unlike Kevei's proofs, ours are based on mainly the Williamson transform.…”
Section: Msc Code: 26a12 60e05mentioning
confidence: 97%